The Bidirectional Spirituality Scale: Construction and Initial Evidence for Validity - W. Paul Williamson; Aneeq Ahmad (Spiritual Psychology and Counseling)
This study presents the development and construction of the 16-item Bidirectional Spirituality Scale (BSS), which is based on the theory of vertical and horizontal spirituality. Vertical spirituality focuses on that involving one’s relationship with God, whereas horizontal spirituality is concerned with one’s relations with people and attunement to meaning and purpose. Using data from 239 USA participants, exploratory factor analysis has produced three factors: vertical spirituality (VS; 8 items); horizontal spirituality-others (HS-O; 4 items); and horizontal spirituality-existential (HS-E; 4 items). A partial confirmatory factor analysis has confirmed the three-factor model. For research purposes, HS-O and HS-E can be combined to produce an 8-item horizontal spirituality scale to complement the 8-item VS scale. Further analyses have found preliminary evidence for both convergent and discriminant validity. Because of its sound psychometric properties, the BSS appears to be a useful, brief instrument for discriminating both religious and non-religious spirituality.